Calcium carbonate pendants in semiarid soils of Rashakan region (Urmia, Iran) and their paleoclimatic significance - Sh. Manafi (Desert, 2019)
Accumulation of secondary calcium carbonates in arid and semiarid regions is a valuable tool for evaluating the degree of soil evolution, soil age, palaeoenvironmental reconstruction, and soil classification. In particular, laminated pedogenic carbonate pendants are able to provide evidence regarding local environmental and climatic changes. In this study, calcitic pendants from semiarid soils of Rashakan region (West Azerbaijan province, Iran) were investigated. Rashakan region is composed of four physiographic units, including mountains, hills, plateaus, and piedmont plains. A transect of four soil profiles was studied micromorphologically. Based on micromorphic observations, carbonatic pendants are present as mammillary to botryoidally stalactite-like masses, growing downwards from the bottom of coarse fragments. They are multilayered and comprised several light and dark-colored layers, indicating the differences in calcite precipitation conditions. Sequences of light and dark-colored lamina of pendants probably represent climatic changes. We propose that light-colored lamina with relatively pure calcite are precipitated in dry periods that climatic conditions are not favorable for biological activities. However, dark-colored lamina, consisting of calcite mixed with clay and organic impurities, are formed in relatively wet periods with better conditions for biological activities. Therefore, the sequence of light and dark-colored laminae can reflect climatic variations and be employed as a tool for palaeoclimatical and palaeoenvironmental studies.  In the structure of some pendants, there exist some fractures and voids between pendant and skeletal grains. Accordingly, these pendants must be considered for palaeoclimatical and palaeoenvironmental reconstructions.